1999
DOI: 10.1037/0893-164x.13.2.98
|View full text |Cite
|
Sign up to set email alerts
|

A clinical profile of women with posttraumatic stress disorder and substance dependence.

Abstract: To assess the clinical characteristics of women with posttraumatic stress disorder (PTSD) and substance dependence, 28 women with both disorders were compared with 29 women with PTSD alone on a wide battery of lifetime and current clinical measures. The dual-diagnosis women consistently had a more severe clinical profile, including worse life conditions (e.g., physical appearance, opportunities in life), both as children and as adults; greater criminal behavior; a higher number of lifetime suicide attempts; a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…5,12,60 Scores for all nine primary dimensions of the BSI as well as the General Symptom Severity Index were significantly higher in SUD women with comorbid PTSD compared to those without PTSD. These findings are congruent with existing literature showing more severe clinical profiles and interpersonal problems in dually diagnosed females compared to females with only one of the two disorders 3,61,62 and call for improved assessment and treatment within this population.…”
Section: Discussionsupporting
confidence: 82%
“…5,12,60 Scores for all nine primary dimensions of the BSI as well as the General Symptom Severity Index were significantly higher in SUD women with comorbid PTSD compared to those without PTSD. These findings are congruent with existing literature showing more severe clinical profiles and interpersonal problems in dually diagnosed females compared to females with only one of the two disorders 3,61,62 and call for improved assessment and treatment within this population.…”
Section: Discussionsupporting
confidence: 82%
“…The rates found in these other studies may be higher because some samples included individuals with drug dependence, which typically begins at a later age than AD, and some were comprised of only women. Similar to the findings of the current study, higher rates of primary PTSD are more often found among women than among men Kessler et al, 1997;Najavits et al, 1999).…”
Section: Clinical Presentationsupporting
confidence: 92%
“…Findings from other studies, including both community and treatment-seeking samples, estimate that PTSD is primary in approximately 65% to 84% of cases among SUD-PTSD individuals (Epstein et al, 1998;Kessler et al, 1997;Najavits et al, 1999). The rates found in these other studies may be higher because some samples included individuals with drug dependence, which typically begins at a later age than AD, and some were comprised of only women.…”
Section: Clinical Presentationmentioning
confidence: 84%
See 1 more Smart Citation
“…The high comorbidity between SUD and PTSD has important clinical implications. Compared to individuals with either disorder alone, patients with comorbid SUD and PTSD show more severe symptoms and worse treatment outcome (Back et al, 2000;Brown & Wolfe, 1994;Najavits, Weiss, & Shaw, 1999;Ouimette, Brown, & Najavits, 1998). It has been suggested that the treatment effects for this patient group can be improved by providing a combined treatment program for SUD and PTSD (Donovan, Padin-Rivera, & Kowaliw, 2001;Driessen et al, 2008;McGovern et al, 2009;Najavits et al, 2007;Rash, Coffey, Baschnagel, Drobes, & Saladin, 2008).…”
Section: Introductionmentioning
confidence: 95%